Use of Combination Intracameral of Mydriatics and Anesthetics vs Topical Mydriatics in Small Incision Cataract Surgeries for Better Pupillary Dilatation. - Huda, Mahmud Ul; Salam, Md Abdus; Zinnurain, Md; Zahin, Abrar; Chowdhury, Md Miftahul Hossain; Sultana, Zakia; Roy, Subarna (Journal of National Institute of Ophthalmology, 2025)
Background: Small incision cataract surgery (SICS) is one of the cost-effective surgical procedures In small incision cataract surgery (SICS) topical mydriatics are used conventionally. Combination of intracameral mydriatics and anesthetics are used in recent years. The aim of this study was to compare efficacy of combination of intra cameral (IC) administration of mydriatics and anesthetics (tropicamide 0.02%, phenylephrine 0.31% and lidocaine 1%) with topical mydriatics (tropicamide 0.8% and phenylephrine 5%) in small incision cataract surgery (SICS). Methods: This is a prospective, interventional study done in Department of Ophthalmology, Sheikh Hasina medical college Hospital, Jamalpur. The study includes 126 eyes of 126 patients who were admitted in the inpatient department of SHMCHJ for cataract surgery from 27 April, 2022 to 24 May, 2022. Patients were randomized into two groups: Intracameral mydriatics (ICM) group and Topical mydriatics (TM) group. IC group received 0.2 ml intra cameral injection of mydriatics and anesthetics just after the first incision and topical group received preoperative topical regimen of one drop each of tropicamide 0.8% and phenylephrine 5% repeated three times. The size of the pupil was measured per operatively with caliper. Results: A total of 126 patients were enrolled. The mean pupil diameter in ICM group was 7.6 mm ± 0.72 before capsulorhexis, 7.3mm ± 0.78 before lens implantation and 7mm ± 0.83 before end of surgery. In case of TM group the diameter was 7.9 mm ± 0.51, 7 mm ±0.68 and 6.7 mm ±0.85 respectively. A pupil diameter ≥ 6mm was achieved and maintained, till the end of surgery, 95.7% in ICM group and 86.3% in TM group. Conclusions: SICS can safely be done with intracameral combination of tropicamide, phenylephrine, and lidocaine as well as can be a good alternative to standard topical regimen. Optimum pupillary diameter is maintained in ICM group which ensures proper mydriasis . J.Natl.Inst.Ophthalmol. 2023; 6(2):32-37